THE METHOD FOR SIMULATION OF CONTINUOUS FUZZY VALUES BASED ON EXPERIMENTAL DATA - Andryushchenko, V. O. (Science and Transport Progress, 2008)
Based on the fuzzy modeling of railway operation processes, the issues of forecasting wagons movement periods have been considered.